Management of internal derangement of Temporomandibular joint with platelet rich plasma: Pilot study (Mustansiria Dental Journal, 2018)
Introduction: Temporomandibular joint internal derangements are progressivepainful conditions that associated with limitation of mouth opening that caused bydisruption within the internal aspects of the TMJ.The aim of this study was to evaluate the management of internal derangementof TMJ regarding pain intensity in temporomandibular joints and muscles ofmastication and mouth opening.Materials and methods: This study was conducted in the Department of oral andmaxillofacial surgery-college of dentistry Tikrit University. Twenty-one patients,14 women and 7men with age range between 18-33 years old, were diagnosedwith internal derangement of TMJ that were treated by intraarticular PRP.Results: show significant reduction of pain experienced by the patient after 12weeks(P- < 0.0001). And show significant improvement of maximal interincisalmouth opening (P-